Development of sustainability optimization tool for pneumatic connector product - Salaam, Hadi Abdul; Zahari, Taha; Daniyal, Hamdan; Romli, Awanis; Che Lah, Nurul Akmal; Shaharudin, Mohd Ali Hanafiah (2020)
Sustainability concept was introduced by Harlem Brundtland consists of three criteria’s; economics, environmental and social. However, recent research on the indicator used had increasingly called into question where the indicator is difficult to be assessed and the measurement is indirect. In the manufacturing industry perspective, manufacturing costs is the measure of company economic sustainability which consists of six cost assessments which include raw material, tool, coolant, lubricant, energy and manpower. Whilst environmental criterion is a measure of the impact of manufacturing activities on the environment such as chip recycling impact and energy impact. The social criteria can be measured by using the production operator health. The ergonomic assessment used is The Revised NIOSH Weight Lifting Index as the method measures the potential impact of the worker during lifting activities. The development of the software/tool is based on Microsoft Excel platform. The present study also highlights the usage of neural network and inversion of the neural network model assessment for the optimization purpose. Minimum values from each criterion were used to obtain the optimum set of cutting parameters. The optimum cutting speed and feedrate results is 55.25 m/min and 0.10 mm/rev for Aluminum 6061 and 82.00 m/min and 0.10 mm/rev for Brass C3604 material.